Searching for ontological security: women's experiences leading to high drive for muscularity. Issue 4 (4th July 2022) - Edwards, Christian; Molnár, Győző; Tod, David
ABSTRACT: Women with high levels of drive for muscularity (DFM) may display what could be perceived as non-normative corporeal desires because their commitment to muscle may contrast Western societal expectations of femininity. Little, however, is known about women's experiences with high levels of DFM. Thus, we explored the stories of women with high DFM and disclose the socio-cultural and personal influences shaping this desire. In-depth life-history interviews were undertaken with 10 females who had extreme scores on the Drive for Muscularity Scale. Participants' stories focused on a set of early social interactions, in which they were exposed to dominant social narratives of femininity. As a result, they felt pressured to comply with contemporary appearance-related gender norms. Such pressures often manifested in situations where their body was perceived to be outside of gendered contours. Participants' narratives also identified the lack of control they had over their circumstances. In turn, participants revealed that they developed a strong desire to gain control over their situation and, as a result, they responded by 'tightly controlling' and shaping their corporeal self as per gendered expectations. However, through a range of problematic moments (e.g. relationship breakdowns), participants' gendered ontological security became unsettled. Consequently, these disruptions prompted them to reconsider their relationship to embodiment and its connection to their circumstances. This realisation led to the emergence of a muscularity-focused coping strategy eventually leading to high levels of DFM. Findings reveal that, similar to men, women in this study also use muscle to cope with and negotiate life events.